2017
DOI: 10.1007/s11096-017-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-management research of asthma and good drug use (SMARAGD study): a pilot trial

Abstract: Background Community pharmacists play an important role in supporting patients for optimal drug use. Objective To assess the effectiveness of monitoring in asthma patients with inhaled corticosteroids (ICS) on disease control. Setting Asthma patients using ICS were invited from two intervention (IG) and two control pharmacies (CG). Method Participating patients completed questionnaires at the study start and at 6-month follow-up, including the Control of Allergic Rhinitis and Asthma Test (CARAT) questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Assessment of user experience revealed that the written instruction did not contain detailed information about the data synchronization protocol, which, combined with instructions at enrolment, may have led to some of the reported observations. In earlier research with the same EIMD, the researchers had presumed the possibility of false-negative as well as false-positive registrations, but they were unable to verify the registrations by patients’ actual inhalations or the data on user interaction with the system to interpret their findings [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of user experience revealed that the written instruction did not contain detailed information about the data synchronization protocol, which, combined with instructions at enrolment, may have led to some of the reported observations. In earlier research with the same EIMD, the researchers had presumed the possibility of false-negative as well as false-positive registrations, but they were unable to verify the registrations by patients’ actual inhalations or the data on user interaction with the system to interpret their findings [15].…”
Section: Discussionmentioning
confidence: 99%
“…An electronic inhalation monitoring device (EIMD), which measures inhalation actuations, provides detailed data on patient adherence to treatment for both patient and health care providers [4-7]. EIMDs, in combination with audiovisual reminders and feedback, have the potential to improve medication adherence and health care outcomes by facilitating self-management and aiding in clinical (shared) decision making [8-15]. Previous studies have shown that involving patients in monitoring their own symptoms can lead to improved awareness and competence in disease management [16].…”
Section: Introductionmentioning
confidence: 99%
“…CARAT has been used in 19 countries globally including developing countries. 22 CARAT can be used in a range of different aims: (a) screening of patients with rhinitis or asthma in different settings including pharmacies, 42 (b) follow-up consultations together with lung function, 43 (c) patient self-management 44 and (d) identifying patients with uncontrolled asthma at pharmacies. 42 It should increase awareness of the level of disease control and strengthen the partnership between patients and doctors in the management of asthma and rhinitis by helping to define shared treatment goals.…”
Section: Characteristicsmentioning
confidence: 99%
“…Digitally enabled inhalers (so-called 'smart inhalers') are also becoming available, which can monitor medication use (time, date, number of inhalations) and, when connected wirelessly to a mobile phone, can send medication alerts/reminders for scheduled doses, which can improve both adherence and asthmarelated health outcomes 90,91 . Data obtained from such devices can be used to deliver self-management interventions tailored to the specific needs of patients, thus increasing the efficacy of such interventions.…”
Section: How Can We Bring Asthma Care Into the Twenty-first Century?mentioning
confidence: 99%